Visualization Of Tourist Visit Time Series Data Using Google Data Studio - Nur Azis; Ahmad Jurnaidi Wahidin; Pandu Adi Cakranegara; Arianto Muditomo; Efendi Efendi (Institute of Computer Science (IOCS), 2022)
Data presentation techniques in the development of information technology are essential in processing data and producing information. The process of processing data into information can be one of the considerations in determining decisions. Time series data containing data with detailed time sequence frequencies within a certain period can be processed into information showing changes in a data variable within a specific period that can be analyzed according to needs, for example, on data on domestic tourist visits in an area. If the data can be adequately visualized, it can provide easy to digest information. Data analysis is carried out on the Google Data Studio interface because combining visualization methods can help people quickly understand the data. This study uses Google Data Studio for data analysis and visualization through scoreboards, line graphs, and pie charts. The results of the research are in the form of data visualization, which shows a decrease in the number of domestic tourist visits to Bali from 2019-2021, which is around 500 thousand domestic tourists from 2019 to 2020, and a decrease of about 30 thousand domestic tourists from 2020 to 2021. In addition, visualization data with pie charts show a decrease in domestic tourist arrivals of 54.2% in 2019. The percentage decreased to 23.6% in 2020 and 22.1% of visits in 2021.